Environmental & architectural phenomenology. Vol. 13, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2002)
Vol. 13, No. 2, Spring 2002 (includes “items of interest,” “citations received,” and essays by Michael Kazanjian, Joel Fajans, Melanie Currie & Gordon Brittan, Jr.).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals